Multiple receptor-mediated functions of activated protein C - Weiler, H. (Hämostaseologie, 2011)
The central effector protease of the protein C pathway, activated protein C (APC), interacts with the endothelial cell protein C receptor, with protease activated receptors (PAR), the apolipoprotein E2 receptor, and integrins to exert multiple effects on haemostasis and immune cell function. Such receptor interactions modify the activation of PC and determine the biological response to endogenous and therapeutically administered APC. This review summarizes the current knowledge about interactions of APC with cell surface-associated receptors, novel substrates such as histones and tissue factor pathway inhibitor, and their implications for the biologic function of APC in the control of coagulation and inflammation.
Keywords: Activated protein C; protein C; anticoagulation; cell signaling; protease activated receptors; apoER2; integrin